Corrections to “TBM-MSE: A Multi-Engine State Estimation Based on Inertial Enhancement for Tunnel Boring Machines in Perceptually Degraded Roadways” - Yu Liu; Hongwei Wang; Lei Tao; Qingxue Huang (IEEE Access, 2024)
In the above article [1], an esteemed author was inadvertently excluded. Qingxue Huang has been appropriately added to the end of the author list.